Teaching the Disembodied: Othering and Activity Systems in a Blended Synchronous Learning Situation - Cunningham, Una (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2014)
This study examines what happens when online and campus students participate in real time in the same campus classroom. Before this study, postgraduate students studying online in a course intended primarily as professional development for language educators were taking the course through reading the course literature including assigned articles, writing reflective texts in the asynchronous forum and doing the course assignments. They had a very different experience than the campus students who met weekly for discussion of the reading. Some online students were not active enough in the course, and showed low levels of engagement. The online students were invited to participate in scheduled campus classes via Skype on iPads. After some hesitation, four of the six online students took up this real-time participation option. Initial difficulties with the technology were addressed after seeking input from campus and online students. A series of adjustments were made and evaluated, including a move to a model in which three online students in different locations participated in a single Skype group video call on a laptop in the campus classroom rather than on multiple individual Skype calls on iPads. After the course, the online and campus students were asked to evaluate the experience of having physical and virtual participants sharing a physical space and to relate this experience to the asynchronous channels previously available to the participants. The comments of both groups of participants were interpreted in the light of previous work on social presence and of activity theory. It appears that student beliefs and student expectations lead to hidden challenges associated with mixing these groups of students, and the study concludes that unless teaching assistance is available, it is not easy to afford online students the same right to speak as campus students.